Peningkatan Kinerja Karyawan Dengan Pelatihan Melalui Kompetensi - Hastuti Indra Sari (Cakrawala Akuntansi & Manajemen, 2022)
The purpose of this research is to analyze employee performance affected by training through competency. Causality research using a quantitative approach. The sampling technique used samples saturated by the number of 40 respondents at PT Pos Indonesia (Persero) Cabang Surabaya Selatan. This research used Structural Equation Model (SEM) with the assistance of smartPLS 3.0 software as the statistical analysis. The results of this research show that employee performance is not affected by training, competence is affected by training significantly and positively, employee performance is affected by competence significantly and positively, and competence can be an intervening variable between training on employee performance.